Implementasi Pendidikan Demokrasi Melalui Pembelajaran Pendidikan Kewarganegaraan Untuk Membentuk Warga Negara Bertanggung Jawab - Ginanjar, Heri; Septiana, Tina (PT. Alahyan Publisher Sukabumi, 2025)
This research is motivated by: (1) The occurrence of deterioration of the learning process that led to the Civics students are less concentrated in the learning process. (2). The tendency of educators who teach science merely poured without a change in attitude and behavior of students. (3). Citizenship Education learning model of creativity among junior high school teachers are still less active, creative and innovative. (4). Education claims that democracy through civic education that teaches covers the development of civic intelligence, civic participation and civic responsibility. Based on that, the researchers conducted a study entitled